Formulation and Characteristic Test of Handbody Lotion Preparation of Pucuk Merah Leaf Extract (Syzygium myrtifolium Walp.) as An Antioxidant (Journal of Tropical Pharmacy and Chemistry, 2025)
Lotions made from natural ingredients are increasingly favored by the public, primarily due to the addition of active compounds that are functional for the skin, such as antioxidants. Antioxidants play an important role in maintaining health by improving skin texture. One potential source of natural antioxidants is the pucuk merah leaf (Syzygium myrtifolium Walp.), which is known to contain phenolic and flavonoid compounds. This study aimed to determine the physical characteristics and antioxidant activity of pucuk merah leaf extract lotion with varying extract concentrations: F1 (0.5%), F2 (2.5%), and F3 (12.5%). The results showed that all formulas met the standards for a good lotion based on organoleptic tests, homogeneity, pH, viscosity, adhesion, spreadability, and emulsion type. Formula 1 was identified as the best formulation based on its organoleptic properties, showing a better dosage form compared to the other formulas. The antioxidant activity was classified as very strong, with IC50 values for each formula being 49.609 ppm (F1), 47.202 ppm (F2), and 35.809 ppm (F3). The antioxidant activity of each formula increased with higher extract concentrations.